2017
DOI: 10.1097/ccm.0000000000002589
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcome of Cancer Patients Admitted to the ICU in England, Wales, and Northern Ireland and National Trends Between 1997 and 2013*

Abstract: Between 1997 and 2013, the outcome of cancer patients with an unplanned admission to ICU improved significantly. Among those admitted between 2009 and 2013, independent risk factors for hospital mortality were age, severity of illness, previous cardiopulmonary resuscitation, previous ICU admission, metastatic disease, and admission for respiratory reasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
56
2
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 43 publications
16
56
2
8
Order By: Relevance
“…The hospital mortality of our study population was similar to other European literature (44%) (3)(4)(5)(24)(25)(26)(27). In contrast, the long-term mortality in our study was higher than in other studies (28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The hospital mortality of our study population was similar to other European literature (44%) (3)(4)(5)(24)(25)(26)(27). In contrast, the long-term mortality in our study was higher than in other studies (28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 86%
“…Over the past two decades, the number of patients with a malignancy requiring intensive care treatment has increased (1). Historically, during the 1980's and 1990's, patients with a malignancy were commonly considered ineligible for intensive care treatment due to their presumed unfavourable outcome (2,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, about two‐thirds of patients involved in the reported errors exhibited low health literacy, communication difficulties or isolation. This finding reflects the general characteristics of patients in ICUs (Ostermann et al, ; Smith et al, ). Further, these patients, compared with other patients, are unstable, require more complicated nursing care and cannot protect themselves (Beccaria et al, ; Garrouste‐Orgeas et al, ; Wittich et al, ).…”
Section: Discussionsupporting
confidence: 59%
“…A systematic review of published outcomes for patients with solid tumours admitted to ICU described an average ICU mortality of 40.1% for patients with lung cancer, the highest of all the individual tumour types described [3]. However, lung cancer is one of the commonest tumour types admitted to ICU [2,6,7].…”
Section: Introductionmentioning
confidence: 99%